2020
DOI: 10.1038/s41392-020-0174-2
|View full text |Cite
|
Sign up to set email alerts
|

CD137 costimulation enhances the antiviral activity of Vγ9Vδ2-T cells against influenza virus

Abstract: Influenza epidemics and pandemics are constant threats to global public health. Although strategies including vaccines and antiviral drugs have achieved great advances in controlling influenza virus infection, the efficacy of these strategies is limited by the highly frequent mutations in the viral genome and the emergence of drug-resistant strains. Our previous study indicated that boosting the immunity of human Vγ9Vδ2-T cells with the phosphoantigen pamidronate could be a therapeutic strategy to treat season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…CD137 (4-1BB) can enhance Vγ9Vδ2 T-cell function following influenza or Listeria infection. Thus, CD137 may also be involved in the antitumor function of γδ T cells 78 , 79 .…”
Section: Regulation Of γδ T Cellsmentioning
confidence: 99%
“…CD137 (4-1BB) can enhance Vγ9Vδ2 T-cell function following influenza or Listeria infection. Thus, CD137 may also be involved in the antitumor function of γδ T cells 78 , 79 .…”
Section: Regulation Of γδ T Cellsmentioning
confidence: 99%
“…In this context, γδ-T cells, a group of unconventional T cells that express the T cell receptor containing a γ and δ chain, display an important role due to their early and rapid response against cellular stress and infections in an major histocompatibility complex (MHC)-independent manner ( 6 ). Although γδ-T cells represent a minor population of T lymphocytes (1–10%) ( 7 , 8 ), they exhibit multiple immunological functions, such as anti-viral infection, inflammation regulation, tissue homeostasis, and even in maintaining successful pregnancy ( 9 13 ). In the early 1990s, some studies suggested that peripheral γδ-T cells play an important role in decreasing natural killer activity through secreting anti-inflammatory cytokines during the whole pregnancy process ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…221,226,227 This subset also strongly relies on CD137 co-stimulation for ideal effector function and expresses high levels of CD69 activation marker in the context of influenza infection. [227][228][229] In other respiratory viral infections, γδT cells also form a fundamental portion of the antiviral innate immune response. During RSV infection, IL-17 expression is impaired in neonates and Vγ4+ γδ T cells adopt an IFN-γ+, proinflammatory cytokine secretome.…”
Section: Roleofγδtcellsinviralrespiratoryinfectionsmentioning
confidence: 99%